Effect of Leadership and Organizational Citizenship Behavior (Ocb) on Work Stress and Employee Performance in Denpasar Tourism Office - Ni Wayan Anggita Dara Pratiwi; I Wayan Gede Suparta; I. B. Ag Dharmanegara (Universitas Warmadewa, 2018)
The purpose of this research is to analyze the influence of leadership, organizational citizenship behavior (ocb) on work stress and employee performance in Denpasar Tourism Office. Hypothesis proposed were 1) Leadership has positive and significant effect on employee performance; 2) Organizational citizenship behavior (ocb) has a positive and significant effect on employee performance; 3) Leadership has a positive and significant effect on work stress; 4) Organizational citizenship behavior (ocb) has a positive and significant effect on work stress; 5) Work stress has a negative and significant effect on employee performance. Research design used is quantitative, with the number of respondents is 51 persons determined by questionnaire method. Data were analysed using SEM based PLS. Results showed that 1) Leadership positively but insignificantly affect the performance of employees; 2) Organizational citizenship behavior has a positive and significant effect on employee performance; 3) Leadership has positive and insignificant effect on work stress; 4) Organizational citizenship behavior (ocb) has positive but insignificant effect on work stress; 5) Work stress has positive and insignificant effect on employee performance.